A Study to Assess the Effectiveness of Education Module on Psychological Stress Experiences and Coping Among Staff Nurses Working in COVID Ward at a Selected Hospital in Bangalore - Feeba Paul (International Journal of Evidence Based Nursing And Practices, 2025)
Occupational stress is a growing concern among healthcare professionals, particularly staff nurses working in COVID wards. The study aimed to explore the sources and effects of occupational stress among staff nurses at Suprabha Hospital, Bangalore, using a pre-experimental one-group pretest-post-test design. 60 staff nurses working in COVID wards were selected through convenient sampling. The results showed that younger nurses, those from joint families, and those with less work experience reported higher stress scores. Additionally, nurses who experienced chronic headaches due to occupational stress showed a significant reduction in stress scores. The study identified four major categories of occupational stressors: working conditions, relationships at work, role conflict and ambiguity, and organizational structure and climate. The findings emphasize the importance of implementing stress management interventions and fostering a healthy work environment for staff nurses within healthcare organizations. This study contributes to the understanding of occupational stress among staff nurses working in COVID wards and informs the development of targeted interventions to mitigate its adverse effects.
Keywords: COVID; convenient sampling; occupational stress; pre-experimental design; stress management interventions